2014
DOI: 10.1111/aos.12550
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival matrix metalloproteinases and their inhibitors in glaucoma patients

Abstract: ABSTRACT.Purpose: Chronic conjunctival inflammation, caused by various reasons, for example long-term use of topical drugs and/or their preservatives, affects the outcome of glaucoma surgery by interfering with wound healing. Matrix metalloproteinases (MMPs) remodel extracellular matrix (ECM) and are involved in the wound healing process. This study was designed to evaluate the conjunctival expression of MMPs and their tissue inhibitors (TIMPs) in the normal eye, primary open-angle glaucoma (POAG) and exfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In our recently published study, we also found increased expressions of certain MMPs and tissue inhibitors of metalloproteinases (TIMPs) in the conjunctival tissue of glaucoma patients (Helin‐Toiviainen et al. ) which may be an indicator of altered tissue ECM remodelling in patient samples and it may further have an influence in the normal wound healing process. Thus, it is possible that there is a connection between chronic inflammation, alterations in tissue remodelling (Helin‐Toiviainen et al.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our recently published study, we also found increased expressions of certain MMPs and tissue inhibitors of metalloproteinases (TIMPs) in the conjunctival tissue of glaucoma patients (Helin‐Toiviainen et al. ) which may be an indicator of altered tissue ECM remodelling in patient samples and it may further have an influence in the normal wound healing process. Thus, it is possible that there is a connection between chronic inflammation, alterations in tissue remodelling (Helin‐Toiviainen et al.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, it is possible that there is a connection between chronic inflammation, alterations in tissue remodelling (Helin‐Toiviainen et al. ; Välimäki & Uusitalo ) expression of extracellular matrix proteins (Välimäki & Uusitalo ) and lipid accumulation resembling a wound healing cascade similar to atherosclerotic plaque formation. These alterations may interfere with the normal wound healing process eventually influencing surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed changes in gene transcription following latanoprost treatment 22 , 50 53 . Thus, at the conclusion of our study, we collected tissues for the analysis of candidate genes in the cornea and iris.…”
Section: Resultsmentioning
confidence: 99%
“…First, we studied only short-term responses to the drugs. Both pilocarpine and ROCK inhibitors can affect the extracellular matrix, 18,36,42,48 so a longer period of evaluation after dosing is required. Second, the doses we used in vitro may differ from those in the eye.…”
Section: Discussionmentioning
confidence: 99%